HUBUNGAN KECEMASAN STATISTIKA DAN PRESTASI AKADEMIK DENGAN PROKRASTINASI AKADEMIK SEBAGAI MODERATOR - Ide Bagus Siaputra; Mustika Nisaa; Lina Natalya (Universitas Negeri Padang, 2022)
Abstract: The contribution of academic procrastination to the relationship between statistical anxiety and student academic achievement. Statistics is one of the subjects that can arouse students anxiety. Statistics anxiety will have an impact on weakening their level of achievement so that students tend to ignore it because of reluctance and this will worsen the level of student achievement. This study aims to examine the role of academic procrastination in the relationship between statistical anxiety and academic achievement. This research was conducted using a quantitative survey method using measuring instruments SAS (Statistics Anxiety Scale), PPS (Pure Procrastination Scale) and the pre-test, pre-UTS, and UTS scores as benchmarks for academic achievement. Participants were 240 students who active 3rd semester students and take measurement of psychology courses in the 2020/2021 academic year. The results showed that academic procrastination did not act as a moderator in the relationship between statistics anxiety and academic achievement. The conclusion is that students who have statistical anxiety reports as well as delay in assignments do not have a significant impact on their academic achievement.Keywords: statistic anxiety, academic achievement, academic procrastination Abstrak: Hubungan Kecemasan Statistika dan Prestasi Akademik dengan Prokrastinasi Akademik Sebagai Moderator. Statistika merupakan salah satu mata kuliah yang dapat membangkitkan kecemasan mahasiswa. Kecemasan mahasiswa terhadap statistika akan berdampak pada pelemahan tingkat kinerja mereka sehingga mahasiswa menjadi cenderung menunda karena adanya keengganan dan hal tersebut akan semakin memperburuk tingkat kinerja mahasiswa. Penelitian ini bertujuan untuk menguji peran prokrastinasi akademik dalam hubungan kecemasan statistika dan prestasi akademik. Penelitian ini dilakukan dengan menggunakan metode kuantitatif survei (N : 240) mahasiswa aktif semester 3 yang tengah mengambil mata kuliah pengukuran psikologi pada tahun ajaran 2020/2021. Data diperoleh dengan menggunakan alat ukur SAS (Statistics Anxiety Scale), PPS (Pure Procrastination Scale) serta nilai pre-test, pre-UTS, dan UTS sebagai tolak ukur prestasi akademik mahasiswa. Penelitian ini menunjukkan hasil bahwa prokrastinasi akademik tidak berperan sebagai moderator pada hubungan kecemasan statistika dan prestasi akademik. Kesimpulannya bahwa mahasiswa yang memiliki kecemasan statistika sekaligus melakukan penundaan dalam mengerjakan tugas tidak berdampak secara signifikan terhadap prestasi akademiknya.Kata kunci : kecemasan statistika, prestasi akademik, prokrastinasi akademik